Perancangan Sistem Informasi Monitoring Penjualan Motor Pada Divisi Digital Marketing - Randy Julyan; Agung Deni Wahyudi (Journal of Artificial Intelligence and Technology Information (JAITI), 2023)
PT Tunas Dwipa Matra (TDM) Honda Raden Intan has problems monitoring motorcycle sales data, especially in the Digital Marketing Division, the Digital Marketing Division is a division that promotes sales through social media such as Facebook, Instagram and TikTok. The Digital Marketing Division has several positions such as Manager, Supervisor, Team Leader and Sales Sales. Every day the Supervisor and Team Leader are required to send a sales report to the Manager via Whatsapp then Sales send a report to the Supervisor and Team Leader respectively via Whatsapp as well. Reports sent such as how many sales today, what units sold, types of credit or cash sales and problems in the sales process. The website-based motorcycle sales monitoring information system is expected that sales data in the Digital Marketing Division will be stored properly, and can be needed at any time, because sales data has been systemized. Then in order to make it easier to determine the amount of stock that must be provided, a sales forecasting method is needed so that it can be a consideration for companies in procuring stock inventory in the future.